Lithuania’s Competitiveness: Myths, Realities and Perspectives - Rojaka, Jekaterina (Ekonomika, 2008)
In recent years, the concept of national competitiveness and favourable business environment is broadly associated with economic development. The countries are increasingly paying attention to their competitiveness on global markets by promoting national programs and founding institutions aimed at tackling competitiveness issues. A number of leading international organizations, research institutes and business entities carry out global comparative studies on nation’s competitiveness. However, the global competitiveness ranking results are often inconsistent with economic trends. This raises a question whether the international competitiveness ran kings provide a proper guidance for an individual economy in improving the business environment. The paper aims at revealing the factors behind the discrepancies in evaluating a national competitiveness by international institutions and national agents. The analysis is based on the datasets of two influential publications - Doing Business (the World Bank) and Global Competitiveness Report (World Economic Forum). The study was enriched by a questionnaire, specially tailored to assess the most problematic issues in measuring the business and investment environment. The research has shown that the international comparisons only partially correspond to the national perception of competitiveness. The paper also addresses policy insights for enhancing Lithuania’s competitiveness.